Fast‐Track Introgression of "QTL‐hotspot" for Root Traits and Other Drought Tolerance Traits in JG 11, an Elite and Leading Variety of Chickpea. Issue 3 (1st November 2013) - Varshney, Rajeev K.; Gaur, Pooran M.; Chamarthi, Siva K.; Krishnamurthy, L.; Tripathi, Shailesh; Kashiwagi, Junichi; Samineni, Srinivasan; Singh, Vikas K.; Thudi, Mahendar; Jaganathan, Deepa
Abstract : A " QTL‐hotspot " containing quantitative trait loci (QTL) for several root and drought tolerance traits was transferred through marker‐assisted backcrossing into JG 11, a leading variety of chickpea ( Cicer arietinum L.) in India from the donor parent ICC 4958. Foreground selection with up to three simple sequence repeat markers, namely TAA170, ICCM0249, and STMS11, and background selection with up to 10 amplified fragment length polymorphism primer combinations was undertaken. After undertaking three backcrosses with foreground and background selection and selfing, 29 BC3 F2 plants homozygous for two markers (ICCM0249 and TAA170) were selected and referred as introgression lines (ILs). Root trait phenotyping of these ILs showed higher rooting depth (RDp) (average 115.21 ± 2.24 cm) in all 29 ILs, better root length density (RLD) (average 0.41 ± 0.02 cm cm −3 ) in 26 ILs, and higher root dry weight (RDW) (average 1.25 ± 0.08 g per cylinder) as compared to the recurrent parent, JG 11 (111.70 cm for RDp, 0.39 cm cm −3 for RLD, and 1.10 g per cylinder for RDW), as well as the donor parent, ICC 4958 (114.20 cm for RDp, 0.45 cm cm −3 for RLD, and 1.25 g per cylinder for RDW). These ILs, developed in 3 yr, after multilocation field trials may be released as improved variety with enhanced drought tolerance.